Assessing the consumer-based brand equity of news media firms: a new validated scale. Issue 3 (3rd July 2018) - Victoria-Mas, María; Lacasa-Mas, Ivan; Marimon, Frederic
ABSTRACT: This article provides a validated scale to measure one of the main competitive advantages of news media firms: consumer-based brand equity (CBBE). A survey of 1175 readers was undertaken. Confirmatory factor analysis was used to analyse the dimensions deployed in the latent CBBE construct, which was examined as a third-order factor composed of functional associations (basic utility and journalistic quality), experiential associations (tone and packaging), and symbolic associations (reliability, ideology, and identity). The construct validity for the CBBE measurement of various types of news media brands and theoretical implications for media branding are also discussed.